Connotation and Realization Path of Labour Education in Universities - Based on the Perspective of Chinese Universities / Zhang Jun Li ... [et al.] - Kimberley Lau, Yih Long; Ma, Xiao Yuan (Universiti Teknologi MARA Cawangan Sarawak, 2021)
Labour education has been weakened and alienated in higher education. Repositioning labour education is an important part of the deepening reform of colleges and universities as well as the focus of improving the higher education system. Practicing labour education can enhance college students’ labour awareness, improve labour skills and enable college students to obtain a rational understanding of ‘knowledge’ from the practice of ‘action’. This is an important way to realize holistic education. This article puts forward the connotation of ‘labour’ under the background of the new era and updates the traditional cognition of ‘labour’. It proposes effective ways for colleges and universities to realize labour education according to the background of the era and the labour demand of employers; so as to break the shortcomings of labour education in colleges and universities as well as improve the quality of whole-person education to better meet the needs of the job market.